Endometrial stromal sarcoma: A review of the literature - Geetha Puliyath; M Krishnan Nair (Indian Journal of Medical and Paediatric Oncology)
Endometrial stromal sarcomas are rare malignant tumors of the uterus, and most of the information available in literature is based on small series or case reports. A proper preoperative diagnosis is difficult and in most cases the diagnosis is confirmed after hysterectomy for a presumed benign disease. Endometrial sampling, ultrasound, and magnetic resonance imaging can provide diagnostic clues. Total hysterectomy with bilateral salpingo-oopherectomy is the main line of management and for early disease complete cure is a reality. Ovarian conservation may be possible in young women with early stage disease and the role of lymphadenectomy is controversial. Adjuvant hormone therapy in the form of progesterone, gonadotropin releasing hormone analogues, and aromatase inhibitors are found to be effective in preventing recurrences. Hormone therapy, radiotherapy and surgical excision of the metastasis are recommended for recurrences.